Rancang Bangun Aplikasi Point Of Sales Berbasis Website Pada Toko Ramai Rambipuji - Tanamal, Rinabi; Mourent, Jefferson (JATISI, 2025)
Toko Ramai Rambipuji is a retail store that manages transactions manually, often leading to errors in transaction calculations, product recording mistakes, and long queues, which hinder operational efficiency. To address these issues, a web-based point-of-sale system will be developed using Laravel as the framework and MySQL as the database, with data collected through interviews and observations, and system testing conducted using unit scenario testing. This application will feature transaction recording, sales report generation, and an intuitive user interface, aiming to enhance operational efficiency, reduce transaction errors, and improve customer service. The originality of this project lies in the tailored implementation of Laravel and MySQL to meet the specific needs of Toko Ramai Rambipuji, providing a relevant and practical digital solution to enhance the store’s competitiveness in the digital era. The test results received positive feedback from the user. They felt that the POS system developed was helpful.